Family conflict and children's learning strengthening parent participation in children's education - Sison, Waldetrudes Montojo (Education quarterly.)
This paper attempts to explore the relationship between family conflict and children's learning with the end in view of identifying content and processes that may strengthen parent's participation in children's education. The first part of the papers covers generalization drawn from a critical review of the literature on family studies and from the author's research on family conflict and chilsdren's learning.